Análisis de las ventas en las Tiendas Industriales Asociadas del cantón Jujan periodo 2019 – 2020 - Bayona Quintana, Yomira Dayana (2021)
This case study tries to analyze how sales have been presented in the Associated Industrial Stores (TIA) of the Jujan canton during the years 2029 and 2020, therefore, it tries to answer questions that lead to a specific conclusion of what happened in this place; What external factors have influenced the sales of the Associated Industrial Stores? What are the perceptions of customers about the Associated Industrial Stores? With the pertinent information that is extracted it will be of great value for the investigation. The investigation was carried out under the qualitative modality that allowed to carry out a detailed review of the phenomenon to be treated, a descriptive investigation was used to know the reality of the study population; scientific, deductive and bibliographic methods were used; The survey technique was applied and a structured questionnaire was developed. This case study is framed in the sub-line of research of the commerce career "Marketing and commercialization".